Effects of drospirenone on adhesion molecule expression and monocyte adherence in human endothelial cells. (June 2016) - Ito, Fumitake; Mori, Taisuke; Takaoka, Osamu; Tanaka, Yukiko; Koshiba, Akemi; Tatsumi, Hiroshi; Iwasa, Koichi; Kitawaki, Jo
Abstract: Objective: A major concern in hormone replacement therapy is the associated increased risk of cardiovascular diseases. A progestogen without the unfavorable effects on cardiovascular disease should be explored. Monocyte adhesion to endothelial cells is an important initial event in atherosclerosis. In this study, the effects of the alternative progestogen drospirenone (DRSP) on monocyte adhesion in human umbilical venous endothelial cells (HUVECs) were examined. Study design: In HUVECs treated with estrogens and progestogens, including DRSP and medroxyprogesterone acetate (MPA), the expression of the adhesion molecules E-selectin, P-selectin, ICAM-1, and VCAM-1 were examined by real-time PCR and using an enzyme-linked immunosorbent assay. A flow chamber system was used to investigate the effects of DRSP on U937 monocytoid cell adherence to HUVEC monolayers. All experimental data were compared using one-way Analysis of Variance. Results: Upregulation of adhesion molecule mRNA or protein was not seen in HUVECs treated with DRSP alone or with 17β-estradiol + DRSP. DRSP alone, 17β-estradiol + DRSP or ethinylestradiol + DRSP did not increase the number of adherent monocytoid cells to HUVECs in the flow chamber system. However, MPA significantly enhanced the monocytoid cell adherence ( P  < 0.05). Conclusions: DRSP did not increase the expression of adhesion molecules or monocytoid cell adherence to endothelial cells, indicating that DRSP could reduce the risk of atherogenesis caused by MPA. These results suggest that DRSP may be an alternative to MPA in hormone replacement therapy.